Education, household income, and depressive symptoms in middle-aged and older Japanese adults - Aya Hinata; Keiko Kabasawa; Yumi Watanabe; Kaori Kitamura; Yumi Ito; Ribeka Takachi; Shoichiro Tsugane; Junta Tanaka; Ayako Sasaki; Ichiei Narita; Kazutoshi Nakamura (BMC, 2021)
Abstract Background Income inequality has dramatically increased worldwide, and there is a need to re-evaluate the association between socio-economic status (SES) and depression. Relative contributions of household income and education to depression, as well as their interactions, have not been fully evaluated. This study aimed to examine the association between SES and depressive symptoms in Japanese adults, focusing on interactions between education and household income levels. Methods This cross-sectional study used data from baseline surveys of two cohort studies. Participants were 38,499 community-dwelling people aged 40-74 years who participated in baseline surveys of the Murakami cohort study (2011-2012) and Uonuma cohort study (2012-2015) conducted in Niigata Prefecture, Japan. Information regarding marital status, education level, household income, occupation, activities of daily living (ADL), and history of cancer, myocardial infarction, stroke, and diabetes was obtained using a self-administered questionnaire. Depressive symptoms were examined using the Center for Epidemiologic Studies Depression Scale (CES-D). Logistic regression analysis was used to obtain odds ratios (ORs). Covariates included age, sex, marital status, education, household income, occupation, ADL, and disease history. Results Individuals with higher education levels had lower ORs (adjusted P for trend = 0.0007) for depressive symptoms, independently of household income level. The OR of the university-or-higher group was significantly lower than that of the junior high school group (adjusted OR = 0.79). Individuals with lower household income levels had higher ORs (adjusted P for trend< 0.0001) for depressive symptoms, independently of education level. The type of occupation was not associated with depressive symptoms. In subgroup analyses according to household income level, individuals with higher education levels had significantly lower ORs in the lowest- and lower-income groups (adjusted P for trend = 0.0275 and 0.0123, respectively), but not in higher- and highest-income groups (0.5214 and 0.0915, respectively). Conclusions Both education and household income levels are independently associated with the prevalence of depressive symptoms, with household income levels showing a more robust association with depressive symptoms than education levels. This suggests that a high household income level may offset the risk of depressive symptoms from having a low education level.